Placental Histomorphometry in Gestational Diabetes Mellitus - Bentley-Lewis, Rhonda (2014)
OBJECTIVES: We examined placental histomorphometry in gestational diabetes mellitus (GDM) for factors associated with race/ethnicity and subsequent type 2 diabetes mellitus (T2DM). METHODS: We identified 124 placentas from singleton, full-term live births whose mothers had clinically defined GDM and self-reported race/ethnicity. Clinical and placental diagnoses were abstracted from medical records. RESULTS: Forty-eight white and 76 nonwhite women were followed for 4.1 years (median, range 0.0-8.9 years). White women developed less T2DM (12.5% vs 35.5%; P = .005) but had higher systolic (mean ± SD, 116 ± 13 vs 109 ± 11 mm Hg; P < .001) and diastolic (71 ± 9 vs 68 ± 7 mm Hg; P = .02) blood pressure, more smoking (35.4% vs 10.5%; P = .004), and more chorangiosis (52.1% vs 30.3%; P = .02) than nonwhite women. CONCLUSIONS: Although more nonwhite women developed T2DM, more white women had chorangiosis, possibly secondary to the higher percentage of smokers among them. Further study is necessary to elucidate the relationship among chorangiosis, subsequent maternal T2DM, and race.